Application of a shunt damping circuit in a structure with an electromagnetically coupled beam: free vibration and frequency response - Minnemann Kuhnert, Willian [UNESP]; Silva, Tarcísio M. P.; De Marqui Junior, Carlos; Cammarano, Andrea; Paupitz Gonçalves, Paulo J. [UNESP] (Springer Nature, 2024)
This paper presents a study on the application of a shunt damping circuit for vibration control in electro-mechanically coupled structures. The effectiveness of this design is demonstrated through experimentation with a cantilever beam featuring a magnet at its tip, moving in a wire coil that is connected to the shunt damping circuit. The study showcases the reduction of beam vibrations under both frequency response and free vibration conditions. Results show that the shunt damping circuit significantly reduces the first peak in frequency response during harmonic excitation. Additionally, the settling time of free vibrations is reduced by adjusting the electrical resistance. The paper uses analytical expressions for achieving critical damping for the free response, along with experimental validation. The study also offers a detailed description of the design process of the negative impedance converter used in the electrical circuit. This includes an examination of the influence of the transducer mass and moment of inertia on the converter's design. Finally, this paper offers valuable insights into the design of shunt damping circuits for vibration control in electro-mechanically coupled structures. The experimental results and analytical expressions provided in the study can help guide the realization of such circuits in various applications.
Keywords: Electromechanics; Shunt circuit; Vibration control